STUDY OF SUSTAINABLE DEVELOPMENT OF MEAT PRODUCT SUBCOMPLEX AND MEAT MARKET IN UKRAINE - SAKHNO, ANDRII; SALKOVA, IRYNA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The importance of the meat product subcomplex in the production of agricultural products is substantiated, which allowed to identify and assess the importance of meat products in domestic markets in the face of growing needs of the population. The need for state support for agricultural production, in particular the development of animal husbandry as a major factor in the existence of meat production. The annual balance of beef, pork, chicken and other animals over the past five years was analyzed, which showed a trend of declining beef and pork production, but increased chicken production. A similar trend is observed for meat consumption per capita - only the production of chicken meat has been growing steadily over the past five years. It is proposed to focus on the organization of such a production and technological chain, which would allow the most efficient use of raw materials, carry out deep processing, expand the range and improve the quality of manufactured products to ensure food security. Opportunities have been identified in the production of poultry meat, which is sold on the domestic market at prices higher than the world, to increase its competitiveness not by increasing state support, but by reducing the cost and improving the quality of meat products. The necessity of capital investment in the development of agricultural enterprises as a basis for the formation of effective activities for the production of meat products, taking into account the social significance for the population of the state.